Quality and Safety in Imaging (Diagnostic Imaging, 2018)
This book provides a roadmap for optimizing quality and safety within radiology practices, whether academic or private and irrespective of their national setting. All aspects of the radiology workflow are addressed, from imaging appropriateness, examination scheduling, and patient preparation through to imaging protocol optimization (including radiation dose management), modality operations, reporting (including structured reporting), and report communication. The book highlights innovative IT tools, including clinical decision support, that drive compliance with national best practice standards and guidelines. The use of big data tools to manage and enhance clinical delivery is addressed. Finally, metrics designed to measure the value that radiology brings to patient care and patient outcomes are introduced. Readers wishing to deepen their understanding of contemporary best practices regarding quality and safety will find this book to be a rich source of practical information.